Study of downhole water sink (DWS) technology to reduce water coning in vertical well [electronic resource] - 426055 Nurlizawati Latif (2006)
Project Paper (Sarjana Muda Kejuruteraan (Petroleum)) - Universiti Teknologi Malaysia, 2006